The use of a mild biocide to reduce biofouling in paper and pulp production processes - Pereira, Maria Olívia (1998)
The paper focuses on biofilm development in paper and pulp mills. A carbamate-based biocide was used to modify the surface properties of the microbial cells in order to promote their attachment to the cellulose fibres and to preventing the bacteria from developing biofilms on the equipment. About 75 % of the cells were retained by the fibres. The effect of glutaraldehyde was also tested and it was concluded that this biocide did not modify the surface charge of the bacteria.